Ecosystem functioning, ecosystem services and rooibos production as affected by connectivity to natural vegetation and agrochemical use in rooibos tea (Aspalathus linearis) farming - Herbst, Marianté (Department of Biological Sciences, 2015)
Globally, increasing land-use intensity has led to more intensive farming practices at the local scale and the loss of non-crop habitats at the landscape scale which may affect various ecosystem services. Insect pollination by wild pollinators is especially affected, but their relative impact and possible interactions have been relatively unexplored. There is also considerable evidence for the negative impacts of agricultural activities and agrochemical use on ecosystem services delivered by natural vegetation, but these impacts have not been assessed for the indigenous crop Aspalathus linearis (rooibos). The study was performed on 13 sites in Nieuwoudtville and Clanwilliam. I found evidence that rooibos pollination is dependent on flying pollinators and that the natural environment is an important provider of ecosystem services to rooibos farmers.